2021
DOI: 10.18632/aging.203798
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid structure stratifies glioma into three distinct tumor subtypes

Abstract: Objective: Tertiary lymphoid structure (TLS), also known as ectopic lymphoid organs, are found in cancer, chronic inflammation, and autoimmune diseases. However, the heterogeneity of TLS in gliomas is unclear. Therefore, it is necessary to identify TLS differences and define TLS subtypes. Methods: The TLS gene profile of 697 gliomas from The Cancer Genome Atlas (TCGA) was used for consensus clustering to identify robust clusters, and the reproducibility of the stratification method was assessed in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…( 21 ), the 40-TLS feature proposed by Zhou et al. ( 23 ), or the 50-TLS feature used by Wu et al. ( 24 ) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 21 ), the 40-TLS feature proposed by Zhou et al. ( 23 ), or the 50-TLS feature used by Wu et al. ( 24 ) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies used several genetic traits relevant to TLS to assess TLS in tissues. Results showed that these traits had different combinations, such as the 9-TLS trait ( 21 ), 12-TLS trait ( 22 ), 40-TLS trait ( 23 ), and 50-TLS trait ( 24 ). We selected these chemokines, developed correlation prediction models, and compared them with our model.…”
Section: Methodsmentioning
confidence: 99%
“…Hypercoagulability and thrombotic complications are common in patients with glioma ( 48 , 49 ). Several previous studies have reported that activation of CCC may be associated with the development of glioma ( 50 - 52 ). However, the specific mechanism of how the CCC is involved in glioma development and the mechanism of coagulation in gliomas has not been enclosed yet.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al. stratified glioma into three distinct tumor subtypes with the gene expression profile of TLS genes ( 28 ). The C subtype glioma with high immune infiltration was poor prognosis without immune checkpoint blockade therapy.…”
Section: Discussionmentioning
confidence: 99%